Additive Manufacturing of a Removable Partial Prosthesis in Titanium Using Binder Jetting Technology: A Brief Research Report - Hagman, Cecilia; Svanborg, Per (Frontiers in Manufacturing Technology, 2022)
Objective: The purpose of this case report was to measure the surface roughness and compare the fit of a cobalt-chromium selective laser melted removable partial denture framework and a titanium binder jetting removable partial denture framework. Material and methods: A design for a removable partial prosthesis framework was made using 3Shape software and thereafter one framework was additively manufactured in cobalt-chromium with selective laser melting and one in titanium using binder jetting technology. The weight of the frameworks was measured and the surface parameters Sa, Sds and Sdr were measured using white light interferometry. The fit of the frameworks was analyzed using visual inspection and pressing test. Results: The weight of the frameworks in their post-printed state was 15,66g and 7,43g for cobalt-chromium and titanium respectively. After finishing and polishing, the cobalt-chromium framework outer surface showed a high shine and smooth surface, with lower values in the Sa and Sdr parameters. The visual inspection showed gaps for the titanium framework and the pressing test detected movement greater than 0.5mm for the same material. Conclusions: The Ti framework showed higher surface roughness and was left with a lackluster finish after polishing. Also, the fit of the Ti framework was not clinically acceptable. The AM binder jetting technology for titanium needs improvement or an adjustment of the settings to be used for clinical removable partial dentures. The cobalt-chromium framework manufactured by selective laser melting showed acceptable clinical fit and surface roughness.